Shwachman–Diamond syndrome: Nationwide survey and systematic review in Japan. Issue 8 (10th July 2018) - Ikuse, Tamaki; Kudo, Takahiro; Arai, Katsuhiro; Fujii, Yoshimitsu; Ida, Shinobu; Ishii, Tomohiro; Mushiake, Sotaro; Nagata, Kouji; Tamai, Hiroshi; Toki, Akira; Tomomasa, Takeshi; Ushijima, Kosuke; et al.
Abstract: Background: Shwachman–Diamond syndrome (SDS) is a rare multisystem disorder associated with exocrine pancreatic insufficiency. The present study reports the results of a nationwide survey and a systematic review on SDS to develop consensus guidelines for intractable diarrhea including SDS. Methods: Questionnaires were sent to 616 departments of pediatrics or of pediatric surgery in Japan in a nationwide survey. A second questionnaire was sent to doctors who had treated SDS patients and included questions on clinical information. Additionally, a systematic review was performed using digital literature databases to assess the influence of medical (i.e. non‐surgical) treatment on SDS prognosis. Results: Answers were received from 529 institutions (85.9%), which included information on 24 patients with SDS (median age, 10.4 years; male, n = 15) treated from January 2005 to December 2014. Although 75% of patients received pancreatic enzyme replacement therapy, there was no significant association between treatment and prognosis. Systematic review identified one clinical practice guideline, two case series, eight case reports and 26 reviews. Patient information from those studies was insufficient for meta‐analysis. Conclusions: The rarity of SDS makes it difficult to establish evidence‐based treatment for SDS. According to the limited information from patients and published reports, medical treatment for malabsorption due to SDS should be performed to improve fat absorption and stool condition, but it is not clear whether this treatment improves the prognosis of malabsorption.